Determination of the Intention of MSMEs Owners Using Sharia Cooperatives in Improving Indonesian Islamic Economic Empowerment - Muhammad Alfarizi; Ngatindriatun (Universitas Airlangga, 2022)
ABSTRAK Penurunan profit bisnis kecil akibat implikasi ekonomi pasca pandemi COVID-19. Persoalan struktur permodalan menjadi kendala dalam mempertahankan dan meningkatkan usahanya secara terus menerus seiring kerubahan zaman. Koperasi Syariah sebagai salah satu lembaga keuangan Islam yang keislaman lebih dekat secara eksistensi maupun teritorial dengan masyarakat tingkat bawah sehingga menjadi alternatif pengembangan usaha masyarakat secara syariah sesuai persyaratan yang diberikan. Studi ini bertujuan untuk untuk menganalisis pengaruh literasi keuangan syariah dalam sikap, pengaruh sosial dan self-efficacy terhadap perilaku pemanfaatan produk koperasi syariah di Indonesia. Studi kuantitatif survey online dengan melibatkan 280 calon anggota koperasi syariah yang membutuhkan pembiayaan dan merupakan pemilik UMKM dijalankan dengan teknik analisis SEM PLS. Hasil studi menunjukkan pengaruh literasi keuangan terhadap sikap, pengaruh sosial dan self-efficacy lalu dilanjutkan arah jalur dukungan hipotesis terhadap niat untuk memilih Koperasi Syariah sebagai solusi kebutuhan finansial UMKM ditemukan. Strategi manajerial khususnya pemasaran dikembangkan dengan mempertimbangkan efek sikap positif, pengaruh sosial dan efikasi diri calon anggota sebagai pemilik bisnis atau produk keuangan syariah yang akan mereka tawarkan kepada pelanggan mereka akan berkontribusi pada pertumbuhan sektor UMKM khususnya UMKM Generasi Millenial dan UMKM Hijau di Indonesia melalui upaya promosi dan kerjasama. Kata Kunci: ASE Model, Ekonomi Islam, Koperasi Syariah, Pemberdayaan, UMKM. ABSTRACT The decline in small business profits due to the post-COVID-19 pandemic economy. The issue of capital structure is an obstacle in maintaining and increasing development continuously in line with the changing times. Sharia cooperatives as one of the Islamic financial institutions are closer in existence and territorially to the lower level of society so that they become an alternative for community business development in accordance with the requirements given. This study aims to analyze the effect of Islamic financial literacy on attitudes, social influence and self-efficacy on the application of Islamic cooperative products in Indonesia. Quantitative study of online surveys involving 280 prospective members of Islamic cooperatives who need financing and are MSME owners carried out with the PLS SEM analysis technique. The results of the study show the effect of financial literacy on attitudes, social influence and self-efficacy, then choosing the direction of hypothesis support for the intention to find Islamic Cooperatives as a solution to the financial needs of MSMEs. Managerial strategies especially marketing that are developed taking into account the effects of positive attitudes, social influence and self-efficacy of prospective members as owners or Islamic financial products that they will offer to their customers will increase the growth of the MSME sector, especially Millennial Generation MSMEs and Green MSMEs in Indonesia through promotional efforts and cooperation. Keywords: ASE Model, Islamic Economics, Sharia Cooperatives, Empowerment, MSMEs. REFERENCES Abourrig, A. (2021). Social influence in predicting Islamic banking acceptance: Evidence from Morocco. International Journal of Accounting, Finance, Auditing, 2(2), 42–56. https://doi.org/10.5281/zenodo.4641472 Ajzen, I. (1991a). The theory of planned behavior. Organizational Behavior and Human Decision Processes, 50(2), 179–211. https://doi.org/10.1016/0749-5978(91)90020-T Ajzen, I. (1991b). The theory of planned behavior. Organizational Behavior and Human Decision Processes, 50(2), 179–211. https://doi.org/10.1016/0749-5978(91)90020-T Al-Awlaqi, M. A., & Aamer, A. M. (2022a). Islamic financial literacy and Islamic banks selection: an exploratory study using multiple correspondence analysis on banks’ small business customers. International Journal of Emerging Markets. https://doi.org/10.1108/IJOEM-09-2021-1354 Al-Awlaqi, M. A., & Aamer, A. M. (2022b). Islamic financial literacy and Islamic banks selection: an exploratory study using multiple correspondence analysis on banks’ small business customers. International Journal of Emerging Markets. https://doi.org/10.1108/IJOEM-09-2021-1354 Albaity, M., & Rahman, M. (2019). The intention to use Islamic banking: An exploratory study to measure Islamic financial literacy. International Journal of Emerging Markets, 14(5), 988–1012. https://doi.org/10.1108/IJOEM-05-2018-0218 Albashir, W. A., Zainuddin, Y., Krupasindhu Panigrahi, S., & Pahang, M. (2018). The acceptance of Islamic banking products in Libya: A theory of planned behavior approach. International Journal of Economics and Financial Issues, 8(3), 105–111. Ali, H. (2019). Purchase decision and repurchase models: Product quality and process analysis (Case study of house ownership credit financing in permata sharia bank Jakarta). Scholars Bulletin, 05(09), 526–535. https://doi.org/10.36348/sb.2019.v05i09.006 Atal, N. U., Iranmanesh, M., Hashim, F., & Foroughi, B. (2022). Drivers of intention to use Murabaha financing: religiosity as moderator. Journal of Islamic Marketing, 13(3), 740–762. https://doi.org/10.1108/JIMA-07-2019-0147 Berakon, I., Aji, H. M., & Hafizi, M. R. (2022). Impact of digital Sharia banking systems on cash-waqf among Indonesian Muslim youth. Journal of Islamic Marketing, 13(7), 1551–1573. https://doi.org/10.1108/JIMA-11-2020-0337 Budiono, A. (2017). Penerapan prinsip syariah pada lembaga keuangan syariah. Law and Justice, 2(1), 54–65. https://doi.org/10.23917/laj.v2i1.4337 Cristea, M., & Gheorghiu, A. (2016). Attitude, perceived behavioral control, and intention to adopt risky behaviors. Transportation Research Part F: Traffic Psychology and Behaviour, 43, 157–165. https://doi.org/10.1016/j.trf.2016.10.004 Daradkah, D., Aldaher, A. A., & Shinaq, H. R. (2020). Islamic financial literacy: Evidence from Jordan. Transition Studies Review, 27(2), 109–123. https://doi.org/10.14665/1614-4007-27-2-009 De Vries, H., & Mudde, A. N. (1998a). Predicting stage transitions for smoking cessation applying the attitude-social influence-efficacy model. Psychology and Health, 13(2), 369–385. https://doi.org/10.1080/08870449808406757 De Vries, H., & Mudde, A. N. (1998b). Predicting stage transitions for smoking cessation applying the attitude-social influence-efficacy model. Psychology and Health, 13(2), 369–385. https://doi.org/10.1080/08870449808406757 Dewi, M. K., & Ferdian, I. R. (2021). Enhancing Islamic financial literacy through community-based workshops: a transtheoretical model. Journal of Islamic Accounting and Business Research, 12(5), 729–747. https://doi.org/10.1108/JIABR-08-2020-0261 Dietrich, A. M., Kuester, K., Müller, G. J., & Schoenle, R. (2022). News and uncertainty about COVID-19: Survey evidence and short-run economic impact. Journal of Monetary Economics, 129, S35–S51. https://doi.org/10.1016/j.jmoneco.2022.02.004 Duong, T., & Duc Le, N. (2021). PLS-SEM approach in measuring the impact of influencing factors on user’s perceived security and trust in e-payment – The case of rural areas in Vietnam. International Journal of Scientific and Research Publications (IJSRP), 11(4), 357–364. https://doi.org/10.29322/ijsrp.11.04.2021.p11249 Dwi Hernanik, N., & Pratikto, H. (2022). Religiusity and bank products and their relationship with decision making in micro small medium business funding in PT Bank Muamalat Indonesia. International Journal of Science, Technology & Management, 3(4), 1202–1210. https://doi.org/10.46729/ijstm.v3i4.532 Etikan, I. (2016). Comparison of Convenience Sampling and Purposive Sampling. American Journal of Theoretical and Applied Statistics, 5(1), 1. https://doi.org/10.11648/j.ajtas.20160501.11 Farrell, L., Fry, T. R. L., & Risse, L. (2016). The significance of financial self-efficacy in explaining women’s personal finance behaviour. Journal of Economic Psychology, 54, 85–99. https://doi.org/10.1016/j.joep.2015.07.001 Fauzi, R. U. A., Saputra, A., & Ningrum, I. I. P. (2022). The effect of religiosity, profit and loss sharing, and promotion on consumer intention to financing in Islamic bank toward trust as an intervening variable. Jurnal Studi Ekonomi Dan Bisnis Islam, 8(1), 1–14. Fessler, P., Silgoner, M., & Weber, R. (2020). Financial knowledge, attitude and behavior: Evidence from the Austrian survey of financial literacy. Empirica, 47(4), 929–947. https://doi.org/10.1007/s10663-019-09465-2 Firdaus, M. S. (2022). Pemberdayaan pesantren melalui pendirian koperasi syariah dalam meningkatkan ekonomi masyarakat empowering islamic boarding school through the establishment of sharia cooperatives in imroving the economy community koperasi simpan pinjam pembiayaan syariah. ALMUJTAMAE: Jurnal Pengabdian Masyarakat, 2(1), 29–36. https://doi.org/10.30997/almujtamae.v2i1.2952 Gijsbers, B., Mesters, I., Knottnerus, J. A., & Van Schayck, C. P. (2006a). Factors associated with the initiation of breastfeeding in asthmatic families: The attitude–social influence–self-efficacy model. Breastfeeding Medicine, 1(4), 236–246. https://doi.org/10.1089/BFM.2006.1.236 Gijsbers, B., Mesters, I., Knottnerus, J. A., & Van Schayck, C. P. (2006b). Factors associated with the initiation of breastfeeding in asthmatic families: The attitude–social influence–self-efficacy model. Breastfeeding Medicine, 1(4), 236–246. https://doi.org/10.1089/BFM.2006.1.236 Hair, J. F., Risher, J. J., Sarstedt, M., & Ringle, C. M. (2019). When to use and how to report the results of PLS-SEM. European Business Review, 31(1), 2–24. https://doi.org/10.1108/EBR-11-2018-0203 Hair, J., Hollingsworth, C. L., Randolph, A. B., & Chong, A. Y. L. (2017). An updated and expanded assessment of PLS-SEM in information systems research. Industrial Management and Data Systems, 117(3), 442–458. https://doi.org/10.1108/IMDS-04-2016-0130 Hair Jr., J. F., Matthews, L. M., Matthews, R. L., & Sarstedt, M. (2017). PLS-SEM or CB-SEM: updated guidelines on which method to use. International Journal of Multivariate Data Analysis, 1(2), 107. https://doi.org/10.1504/ijmda.2017.10008574 Hakim, L., & Kurnia, A. (2022). Tafsir riba di media sosial perspektif Roy Shakti dan Arli Kurnia. EKOMA: Jurnal Ekonomi, Manajemen, Akuntansi, 1(2), 312–325. Hartono, H., & Ardini, R. (2022). The effect of opportunity recognition and organization capability on SME performance in Indonesia moderated by business model innovation. The Winners, 23(1), 35–41. https://doi.org/10.21512/tw.v23i1.6932 Hasanah, U., & Lubis, S. D. (2022). Penerapan asas kebebasan berkontrak dalam akad pembiayaan mudharabah pada bank syariah Indonesia kantor cabang pembantu Asahan. Taqmin: Jurnal Syariah Dan Hukum, 11(1), 81–92. https://doi.org/10.37893/jbh.v11i1.683 Hayati, S. R. (2019). Strategi bank syariah dalam meningkatkan literasi keuangan syariah pada masyarakat (Studi Kasus pada BPRS Madina Mandiri Sejahtera). JESI (Jurnal Ekonomi Syariah Indonesia), 8(2), 129. https://doi.org/10.21927/jesi.2018.8(2).129-137 Hendrik, S., Iwan, T., Dedi, M. A., & Zaki, B. (2018). Evidence from Indonesia: Is it true that mudharabah financing and micro business financing are at high risk for sharia banking business? RJOAS, 6(June), 197–205. Hikmawati, T. S., & Muharam, H. (2022). The capital market response to the information content of the announcement of Indonesia entering a recession in 2020 and free of recession in 2021 in the covid-19 pandemic. Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 5(2), 16019–16027. https://doi.org/https://doi.org/10.33258/birci.v5i2.5518 16019 Hoque, M. N., Rahman, M. K., Said, J., Begum, F., & Hossain, M. M. (2022). What factors influence customer attitudes and mindsets towards the use of services and products of Islamic banks in Bangladesh? Sustainability (Switzerland), 14(8). https://doi.org/10.3390/su14084703 Hutomo Mukti, H. (2020). Development of Indonesian sharia banks with Malaysia comparation method (Study of history, products and legal assets). Lambung Mangkurat Law Journal, 5(1), 75. https://doi.org/10.32801/lamlaj.v5i1.140 Im, I., Hong, S., & Kang, M. S. (2011). An international comparison of technology adoption: Testing the UTAUT model. Information & Management, 48(1), 1–8. https://doi.org/10.1016/J.IM.2010.09.001 Irwansyah, S., & Alam, A. P. (2022). Analisis penggunaan akad pada produk pembiayaan multijasa pada PT. Bank Sumut Syariah KCP Stabat. Jurna Islahiyah, 1. Izuma, K. (2017). The neural bases of social influence on valuation and behavior. In Decision neuroscience: An integrative perspective (pp. 199–209). Academic Press. https://doi.org/10.1016/B978-0-12-805308-9.00016-6 Jaffar, M. A., & Musa, R. (2014). Determinants of attitude towards Islamic financing among halal-certified micro and SMEs: A preliminary investigation. Procedia - Social and Behavioral Sciences, 130, 135–144. https://doi.org/10.1016/j.sbspro.2014.04.017 Jaffar, M. A., & Musa, R. (2016). Determinants of attitude and intention towards Islamic financing adoption among non-users. Fifth International Conference on Marketing and Retailing, 37(16), 227–233. https://doi.org/10.1016/s2212-5671(16)30118-6 Khairi, M. S., & Baridwan, Z. (2015). An empirical study on organizational acceptance accounting information systems in sharia banking. The International Journal of Accounting and Business Society, 23(1), 19. https://doi.org/10.1109/hicss.2000.926665 Lechner, L., & De Vries, H. (1995a). Starting participation in an employee fitness program: Attitudes, social influence, and self-efficacy. Preventive Medicine, 24(6), 627–633. https://doi.org/10.1006/PMED.1995.1098 Lechner, L., & De Vries, H. (1995b). Starting participation in an employee fitness program: Attitudes, social influence, and self-efficacy. Preventive Medicine, 24(6), 627–633. https://doi.org/10.1006/PMED.1995.1098 Leguina, A. (2015). A primer on partial least squares structural equation modeling (PLS-SEM). International Journal of Research & Method in Education, 38(2), 220–221. https://doi.org/10.1080/1743727x.2015.1005806 Madeira, C., & Margaretic, P. (2022). The impact of financial literacy on the quality of self-reported financial information. Journal of Behavioral and Experimental Finance, 34, 100660. https://doi.org/10.1016/j.jbef.2022.100660 Mamman, M., Ogunbado, A. F., & Abu-bakr, A. S. (2016). Factors influencing customer’s behavioral intention to adopt Islamic banking in Northern Nigeria: A proposed framework. Journal of Economics and Finance, 7(1), 51–55. https://doi.org/10.9790/5933-07135155 Mardian, S. (2019). Tingkat kepatuhan syariah di lembaga keuangan syariah. Jurnal Akuntansi Dan Keuangan Islam, 3(1), 57–68. https://doi.org/10.35836/jakis.v3i1.41 Memon, M. A., T., R., Cheah, J.-H., Ting, H., Chuah, F., & Cham, T. H. (2021). PLS-SEM statistical programs: A Review. Journal of Applied Structural Equation Modeling, 5(1), i–xiv. https://doi.org/10.47263/jasem.5(1)06 Mindra, R., Bananuka, J., Kaawaase, T., Namaganda, R., & Teko, J. (2022). Attitude and Islamic banking adoption: Moderating effects of pricing of conventional bank products and social influence. Journal of Islamic Accounting and Business Research, 13(3), 534–567. https://doi.org/10.1108/JIABR-02-2021-0068 Mirzaei, M., & Buer, T. (2022). First results on financial literacy in Oman. Managerial Finance, 48(2), 1–17. https://doi.org/10.1108/MF-09-2021-0456 Mukti, T., Shohiha, T. A., Garbo, A., & Latifah, S. (2022a). The effect of sharia financial literacy on the decision of the use of service products in the sharia pawn in Yogyakarta. The 3rd International Conference on Advance & Scientific Innovation (ICASI) Volume 2022 Research, 2022(1), 273–284. https://doi.org/10.18502/kss.v7i10.11365 Mukti, T., Shohiha, T. A., Garbo, A., & Latifah, S. (2022b). The effect of sharia financial literacy on the decision of the use of service products in the sharia pawn in Yogyakarta. The 3rd International Conference on Advance & Scientific Innovation (ICASI) Volume 2022 Research, 2022(1), 273–284. https://doi.org/10.18502/kss.v7i10.11365 Nimfa, D. T., Abdul Wahab, S., Shaharudin Abdul Latiff, A., & Abd Wahab, S. (2021). Theories underlying sustainable growth of small and medium enterprises. African Journal of Emerging Issues (AJOEI). Online ISSN, 3, 43–66. Nugroho, A. P., Hidayat, A., & Kusuma, H. (2017a). The influence of religiosity and self-efficacy on the saving behavior of the Islamic banks. Banks and Bank Systems, 12(3), 35–47. https://doi.org/10.21511/bbs.12(3).2017.03 Nugroho, A. P., Hidayat, A., & Kusuma, H. (2017b). The influence of religiosity and self-efficacy on the saving behavior of the Islamic banks. Banks and Bank Systems, 12(3), 35–47. https://doi.org/10.21511/bbs.12(3).2017.03 Ouachani, S., Belhassine, O., & Kammoun, A. (2021). Measuring financial literacy: A literature review. Managerial Finance, 47(2), 266–281. https://doi.org/10.1108/MF-04-2019-0175 Purwantini, A. H., Noor Athief, F. H., & Waharini, F. M. (2020). Indonesian consumers’ intention of adopting Islamic financial technology services. Shirkah: Journal of Economics and Business, 5(2), 171. https://doi.org/10.22515/shirkah.v5i2.304 Purwanto, A., & Sudargini, Y. (2021). Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis for social and management research: A literature review. Journal of Industrial Engineering & Management Research, 2(4), 114–123. Rahman, S. A., Tajudin, A., & Tajuddin, A. F. A. (2018a). Determinant factors of Islamic financial literacy in Malaysia. American Journal of Humanities and Social Sciences Research, 2(10), 125–132. Rahman, S. A., Tajudin, A., & Tajuddin, A. F. A. (2018b). Determinant factors of Islamic financial literacy in Malaysia. American Journal of Humanities and Social Sciences Research, 2(10), 125–132. Rai, N., & Thapa, B. (2015). A study on purposive sampling method in research. In Kathmandu Publisher (1st ed.). Kathmandu School of Law. Rasheed, R., & Siddiqui, S. H. (2022). SMEs behavioral intention towards usage of financial products: A comparative study of Islamic and conventional Banks in Pakistan. Sustainable Business and Society in Emerging Countries, 4(1), 141–150. Razak, D. A., & Abduh, M. (2012a). Customers’ attitude towards diminishing partnership home financing in Islamic banking. American Journal of Applied Sciences, 9(4), 593–599. Razak, D. A., & Abduh, M. (2012b). Customers’ attitude towards diminishing partnership home financing in Islamic banking. American Journal of Applied Sciences, 9(4), 593–599. Rigdon, E. E., Sarstedt, M., & Ringle, C. M. (2017). On comparing results from CB-SEM and PLS-SEM: Five perspectives and five recommendations. Marketing ZFP, 39(3), 4–16. https://doi.org/10.15358/0344-1369-2017-3-4 Rini, E. E. D. S. (2022). Pengaruh promosi, penerapan prinsip syariah dan bagi hasil terhadap keputusan menjadi bank BNI syariah cabang Pasuruan. An-Nisbah: Jurnal Perbankan Syariah, 33(1), 1–12. Rokhman, W., & Abduh, M. (2020). Antecedents of SMEs’ satisfaction and loyalty towards Islamic microfinance: Evidence from Central Java, Indonesia. Journal of Islamic Marketing, 11(6), 1327–1338. https://doi.org/10.1108/JIMA-05-2018-0090 Safe’i, A. (2012). Koperasi syariah: Tinjauan terhadap kedudukan dan peranannya dalam pemberdayaan ekonomi kerakyatan. Media Syariah, 14(1), 39–62. Sarstedt, M., Hair, J. F., Cheah, J. H., Becker, J. M., & Ringle, C. M. (2019). How to specify, estimate, and validate higher-order constructs in PLS-SEM. Australasian Marketing Journal, 27(3), 197–211. https://doi.org/10.1016/j.ausmj.2019.05.003 Saygılı, M., Durmuşkaya, S., Sütütemiz, N., & Ersoy, A. Y. (2022a). Determining intention to choose Islamic financial products using the attitude–social influence–self-efficacy (ASE) model: the case of Turkey. International Journal of Islamic and Middle Eastern Finance and Management. https://doi.org/10.1108/IMEFM-11-2020-0569 Saygılı, M., Durmuşkaya, S., Sütütemiz, N., & Ersoy, A. Y. (2022b). Determining intention to choose Islamic financial products using the attitude–social influence–self-efficacy (ASE) model: the case of Turkey. International Journal of Islamic and Middle Eastern Finance and Management. https://doi.org/10.1108/IMEFM-11-2020-0569 Sevriana, L., Febrian, E., Anwar, M., & Ahmad Faisal, Y. (2022). A proposition to implement inclusive Islamic financial planning in Indonesia through bibliometric analysis. Journal of Islamic Accounting and Business Research. https://doi.org/10.1108/JIABR-01-2022-0022 Shabrina, Z., Yuliati, L. N., & Simanjuntak, M. (2018). The effects of religiosity, pricing and corporate image on the attitude and the intention to use sharia micro financing. Indonesian Journal of Business and Entrepreneurship, 4(2), 197–206. https://doi.org/10.17358/ijbe.4.2.197 Sitepu, C. F., & Hasyim, H. (2018). Perkembangan ekonomi koperasi di indonesia. Niagawan, 7(2), 59–68. https://doi.org/10.24114/niaga.v7i2.10751 Srisusilawati, P., Malik, Z. A., Silviany, I. Y., & Eprianti, N. (2021). The roles of self-efficacy and sharia financial literacy to SMEs performance: business model as an intermediate variable. F1000Research, 10(May), 1310. https://doi.org/10.12688/f1000research.76001.1 Sumiyati, Y., Januarita, R., Ramli, T. A., & Yusdiansyah, E. (2021a). Konstruksi hukum terhadap penetapan bunga tinggi pada investasi yang diselenggarakan koperasi simpan pinjam. Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 10(2), 385. https://doi.org/10.24843/jmhu.2021.v10.i02.p14 Sumiyati, Y., Januarita, R., Ramli, T. A., & Yusdiansyah, E. (2021b). Konstruksi hukum terhadap penetapan bunga tinggi pada investasi yang diselenggarakan koperasi simpan pinjam. Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 10(2), 385. https://doi.org/10.24843/jmhu.2021.v10.i02.p14 Syamsiyah, N., Syahrir, A. M., & Susanto, I. (2019). Peran koperasi syariah baitul tamwil muhammadiyah terhadap pemberdayaan usaha kecil dan menengah di Bandar Lampung. Al Amin: Jurnal Kajian Ilmu Dan Budaya Islam, 2(1), 63–73. https://doi.org/10.36670/alamin.v2i1.17 Takidah, E., & Kassim, S. (2021). Determinants of Islamic financial inclusion in Indonesia: A demand-side analysis. Journal of Islamic Finance, 10(2), 38–52. Venkatesh, V. (2022). Adoption and use of AI tools: A research agenda grounded in UTAUT. Annals of Operations Research, 308(1–2), 641–652. https://doi.org/10.1007/s10479-020-03918-9 Vidia Khairunnisa, B., & Hendratmi, A. (2019). The influence of product knowledge and attitude towards intention in mudharabah funding products in sharia banks in Mataram. KnE Social Sciences, 3(13), 663. https://doi.org/10.18502/kss.v3i13.4239 Widityani, S. F., Faturohman, T., Rahadi, R. A., & Yulianti, Y. (2020). Do socio-demographic characteristics and Islamic financial literacy matter for selecting Islamic financial products among college students in Indonesia? Journal of Islamic Monetary Economics and Finance, 6(1), 51–76. https://doi.org/10.21098/jimf.v6i1.1057 Yuniar, A., Talli, A. H., & Kurniati, K. (2021). Bisnis koperasi syariah di Indonesia. Al-Azhar Journal of Islamic Economics, 3(2), 79–88. https://doi.org/10.37146/ajie.V3i2.103 Zaman, Z., Mehmood, B., Aftab, R., Shahid, M., & Ameen, Y. (2017). Role of Islamic financial literacy in the adoption of Islamic banking services: An empirical evidence from Lahore, Pakistan. Journal of Islamic Business and Management (JIBM), 7(2), 230–247. https://doi.org/10.26501/jibm/2017.0702-006 Ziky, M., & Daouah, R. (2019). Exploring small and medium enterprises’ perceptions towards Islamic banking products in Morocco. International Journal of Economics and Finance, 11(10), 106. https://doi.org/10.5539/ijef.v11n10p106